Rising tides: adaptation policy alternatives for coastal residential buildings in Australia. Issue 4 (2nd April 2016) - Wang, Chi-Hsiang; Baynes, Tim; McFallan, Stephen; West, Jim; Khoo, Yong Bing; Wang, Xiaoming; Quezada, George; Mazouz, Salim; Herr, Alexander; Beaty, R. Matthew; Langston, Art; Li, Yun; et al.
Abstract : In this work, a risk-based assessment method and benefit-cost analysis to support policy decisions for adapting Australian coastal residential buildings to future coastal inundation hazard is presented. Future coastal inundation is mainly influenced by storm surge and rising sea level. The sea level rises projected by the A1FI, A1B and B1 emissions scenarios developed by the Intergovernmental Panel on Climate Change are considered. The effects of economic and population growth are accounted for by three urban development scenarios: (a) business as usual, (b) urban consolidation and (c) regional development. The adaptation policy actions investigated include a 'protect' stance (involving the construction of seawalls), an 'accommodate' stance that mandates raising house floors to a certain height (e.g. at heights of 100-year events) and an 'avoid' stance that limits new developments in hazardous areas. Policy stances classified as reactive (i.e. action taken after damage being incurred) and anticipatory (i.e. action taken anticipating what will happen) are developed for asset investment choices. In general, adaptation costs are an order of magnitude lower than benefits gained from avoided damages. The results highlight that adaptation action for coastal inundation has a no-regrets character and provides a strong case for reform to ensure that Australia-wide adaptation opportunities are realised.